La re-presentación, un producto de la experiencia sensible con el mundo del lenguaje (2011)
ABSTRACT: The subject of the representation is crossed by the contemporary aesthetic perspective. Said perspective, has its theoretical fundamentals on Kant, teaches that the representation designates the relationship between sensitivity and conscience, since the subject perceives what he/she-self has created only at mediation moment, namely, when he/she confronts his/her internal reality with the external world. Now then, the bet of the present text is to show that in the field of Freudian psychoanalysis, the conception of the representation that is influenced by the socalled Kantians and Nietzscheans, involves the transposition from nervous excitation to the linguistic image, what is exactly a process of the psychical system, which means, a work of the unconscious thought.